Determinación predicción de las principales propiedades físicas de los fluidos de uso alimentario: viscosidad, conductividad térmica y difusividad - Rojas Donayre, Angela Edelmira (2022)
Momentum, heat transfer and mass transfer are transport phenomena in the food industry. the main physical properties of fluids (gases and liquids). such as: viscosity, density, thermal conductivity, diffusivity, determine the behavior of fluids in fluid mechanics. Knowing the properties of the fluids, the appropriate treatment can be applied for their transformation or conservation in the food industry. Viscosity is a property of fluids where it shows its degree of resistance to flow, depending on the magnitude of the force or shear stress that is applied to it. Heat transfer in food processing, heating and cooling are the most common processes in a food processing plant. It is common to find refrigeration, freezing, sterilization, drying and/or curing units in the modern food industry. Material transfer, in food processing it is often possible to select certain chemical reactions by choosing the ideal conditions and therefore obtain the desired products from the most efficient material possible. However, different by-products are usually produced in addition to the desired products.